Проблеми інтеграційних процесів між Україною та ЄС - Посохов, Ігор Михайлович; Овчаренко, Андрій Іванович; Гусарова, Дар'я Михайлівна (ТОВ "Міжнародний бізнес центр", 2024)
Устатті розглянуто проблеми інтеграційних процесів між Україною та ЄС. Синтезовано результати експертних опитувань стосовно впливу Угоди про асоціацію. Виокремлено основні проблеми в реалізації секторів Угоди про асоціацію: корупція та тіньова економіка, недостатній захист прав інтелектуальної власності, порушення у сфері державних закупівель, відсутність реальних та діючих заходів з підвищення енергоефективності, відсутність реальних шляхів стимулювання екологічно безпечних виробництв.

The paper examines the problems of integration processes between Ukraine and the EU. The purpose of the paper is to generalize the theoretical aspects of economic integration, to highlight the existing problems of economic integration of Ukraine in the EU. Changes in the economic and political vector of Ukraine's development have significantly affected internal processes in the country, economic integration means compliance by Ukraine with certain requirements that should help it integrate into the EU economic space in various directions. Economic integration has always been one of the key issues in foreign countries. Some states are constantly trying to create economic associations for the development of foreign economic activity. This is primarily related to issues of economic security of states. Implementation of the Association Agreement is associated with certain problems. Undoubtedly, the state of war makes adjustments to this process, but even before that, the business side expressed certain comments regarding the implementation of the Agreement. The results of expert surveys on the impact of the Association Agreement, assessments of the future impact of the Association Agreement, the main obstacles to export and import have been synthesized. The main problems in the implementation of sectors of the Association Agreement are highlighted: corruption and shadow economy, insufficient protection of intellectual property rights, violations in the field of public procurement, lack of real and effective measures to increase energy efficiency, lack of real ways to stimulate environmentally safe production, low social security of the population, incomplete use of regulatory mechanisms for stimulating innovative development.
Problems of integration processes between Ukraine and the EU
Keywords: інтеграція; ЄС; товарооборот; міжнародний бізнес; міжнародна торгівля; проблеми; членство в ЄС; integration; EU; international trade; international business; trade; macroeconomic problems; EU membership